Pengaruh Penyuluhan terhadap Pengetahuan tentang Bahaya Penyalahgunaan Lem Aibon pada Remaja di Kelurahan Kofkerbu Kota Sorong - Loihala, Maria; Raka, I Made (An Idea Health Journal, 2021)
Counseling is a behavior that results from the educational process or lessons to make changes, including knowledge about the dangers of aibon glue abuse in adolescents. The research method used is experimental research with a pre-experimental design through a one group pretest posttest design, this study only uses one group, the number of samples in this study is 40 people, the location of the research is in the Kofkerbu Village, Sorong Regency in April-May 2020, the collection technique data through primary data and secondary data, the instrument used was adopted from Riri Apriani's research with the Gutmann scale, the data were analyzed using SPSS Version 23 software. with a mean rank or an average increase in knowledge of 17.00 while a positive rank (sum of rank) is 561,000, then Ha is accepted or there is an influence of counseling on knowledge about the dangers of misuse of aibon glue in adolescents in Kofkerbu Village, Sorong City.